2014
DOI: 10.4172/2161-0509.1000142
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 Deficiency in Pregnancy and Lactation: Is there a Need for Pre and Post-natal Supplementation?

Abstract: This article reviews vitamin B12 (B12) status and deficiency during pregnancy and lactation, its effect on pregnancy, and the health of the offspring, with the aim to underscore the need for a sustainable strategy to improve maternal and infant vitamin B12 status of low and middle income countries. Vitamin B12 is a basic nutrient required for maintenance of normal erythropoiesis, cell reproduction, nucleoprotein and myelin synthesis. B12 deficiency is associated with adverse pregnancy outcomes and neurodevelop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 78 publications
0
9
0
2
Order By: Relevance
“…Evidence also suggests that vitamin B12 concentration gradually decline throughout gestation, therefore, it is challenging to assess the prevalence of deficiency in pregnant women. Studies have shown that based on gestational week, prevalence of vitamin B12 deficiency may vary from 5% (< 28 days gestation) to 72% (immediately prior to delivery) worldwide [38]. The JiVitA study in rural north-western Bangladesh found a prevalence of 20% deficiency in early pregnancy [39].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence also suggests that vitamin B12 concentration gradually decline throughout gestation, therefore, it is challenging to assess the prevalence of deficiency in pregnant women. Studies have shown that based on gestational week, prevalence of vitamin B12 deficiency may vary from 5% (< 28 days gestation) to 72% (immediately prior to delivery) worldwide [38]. The JiVitA study in rural north-western Bangladesh found a prevalence of 20% deficiency in early pregnancy [39].…”
Section: Discussionmentioning
confidence: 99%
“…Hypotonic muscles, failure to thrive, cerebral atrophy, and developmental regression are general outcomes of deficiency of vitamin B12. Folic acid supplemented pregnant women with negative B12 balance have increased risk for adverse maternal and infant outcomes (e.g., increased cardiometabolic disease risk) while pregnant women with Low B12 and a normal-to-high range of folate have high insulin resistance and adiposity in the offspring at 5 years of age [15].…”
Section: Pernicious Anemiamentioning
confidence: 99%
“…The newborn may create paleness because of low iron stores in the body. [38]. During pregnancy, anemia can cause serious complications maternal as well as in newborn childlike unexpected labor and post-pregnancy anxiety.…”
Section: Effect On Young Ones and Effect On Mothermentioning
confidence: 99%
“…Defisiensi vitamin B12 utamanya terjadi pada kelompok lanjut dengan laporan sekitar 40% populasi ini terlibat (Tucker et al, 2000). Kelompok yang juga rentan mengalami kondisi ini adalah ibu hamil dan menyusui dengan perkiraan prevalensi 27-46% di negara berkembang (J Siddiqua, 2014).…”
Section: Pendahuluanunclassified